THE EXPERIMENTAL ECONOMICS OF RELIGION. (12th January 2012) - Hoffmann, Robert
Abstract: This paper surveys the experimental economics approach to the study of religion. The field has a place in the context of the scientific study of religion generally and the social psychology of religion in particular, but employs distinct economic methods which promise new and different insights. In particular, certain features of the experimental approach as used by economists such as incentive compatibility are particularly appropriate for studying the effect of religion on individual behaviour. The paper discusses results obtained so far in terms of two roles of religion in shaping individual behaviour, that is, as a social group identifier and as a set of values.